Lightweight ceramic bearing and manufacturing method thereof
By combining C/C-SiC ceramic materials and Si3N4 ceramic spheres, lightweight ceramic bearings were fabricated, solving the problems of high density in traditional metal bearings and high brittleness in ceramic materials. This enabled lightweight and high-performance applications in special environments such as spacecraft.
Patent Information
- Application Number
- CN202511848281.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-08-22
- Filing Date
- 2025-12-09
- Publication Date
- 2026-02-10
AI Technical Summary
Traditional metal bearings have high density, limited strength and hardness, and insufficient high-temperature resistance, wear resistance and corrosion resistance, making it difficult to meet the lightweight and impact resistance requirements of aerospace and other fields; commonly used ceramic materials are brittle and have low toughness, making it difficult to further reduce density, which limits their application in the aerospace field.
The inner and outer rings are made of C/C-SiC ceramic material, the ceramic balls are made of Si3N4 ceramic material, and the cage is made of polytetrafluoroethylene material. The liquid precursor is prepared by wet dispersion and dry mixing, the fiber preform is woven using a three-dimensional braiding machine, and C/C-SiC ceramic is formed by vacuum silicon infiltration sintering. Combined with high-temperature opening treatment, a lightweight ceramic bearing is prepared.
It significantly reduces bearing weight, improves toughness and wear resistance, and can work stably in ultra-high temperature and ultra-low temperature environments, reducing friction and wear. It is suitable for special environments such as spacecraft and space stations, meeting the requirements for lightweighting.
Smart Images

Figure CN121497726A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of bearings, and more specifically to a lightweight ceramic bearing and its manufacturing method. Background Technology
[0002] Bearings are indispensable key components in modern mechanical equipment, and their performance parameters directly determine the overall machine's operating accuracy, efficiency, and service life. With the continuous development of technologies in high-end fields such as aerospace, increasingly stringent lightweight requirements are being placed on core components such as bearings to meet the operational needs of equipment in extreme environments.
[0003] Traditional metal bearings have been widely used in the mechanical field due to their good toughness and excellent machinability, but they also have many inherent defects: on the one hand, metal materials have a high density, which makes it difficult to meet the requirements of lightweight components in the aerospace field; on the other hand, their strength and hardness are relatively limited, and they do not perform well in terms of high temperature resistance, wear resistance and corrosion resistance, making them unable to adapt to the increasingly complex working conditions in modern science and technology and industrial production.
[0004] To overcome the shortcomings of traditional metal bearings, ceramic materials are increasingly being applied in bearing manufacturing. Ceramic bearings possess significant advantages such as low density, high strength and hardness, high temperature resistance, strong wear resistance, excellent corrosion resistance, and low operating noise. Therefore, using ceramic materials to manufacture bearings has become an important direction for the development of special bearings in the aerospace field. However, commonly used traditional ceramic materials such as silicon nitride and silicon carbide still have significant shortcomings when applied to bearing manufacturing: these materials are brittle and have low toughness, making them prone to fracture under impact or alternating loads. Furthermore, their density is difficult to further reduce, limiting the further application of ceramic bearings in aerospace and other fields with extremely high requirements for lightweight and impact resistance. Summary of the Invention
[0005] To address the above problems, this invention proposes a lightweight ceramic bearing and its manufacturing method, the specific technical solution of which is as follows: A lightweight ceramic bearing includes an inner ring, an outer ring, a cage, and ceramic balls. The inner and outer rings are both made of C / C-SiC ceramic material, the ceramic balls are made of Si3N4 ceramic material, and the cage is made of polytetrafluoroethylene (PTFE). The raw materials for the C / C-SiC ceramic material include hyperbranched polycarbosilane, divinylbenzene, xylene, carbon fibers, phenolic resin, and silicon powder. The C / C-SiC ceramic material has a carbon fiber skeleton network structure and a SiC matrix that wraps the fiber bundles of the skeleton network structure. The SiC matrix is obtained by reacting hyperbranched polycarbosilane and silicon powder that have penetrated into the skeleton network structure with carbon. Free carbon is filled in the pores of the SiC matrix.
[0006] Furthermore, in the raw materials of C / C-SiC ceramic materials, the diameter of carbon fibers is 7μm; the solid content of phenolic resin is ≥50%, and the free phenol content of phenolic resin is ≤15%; the purity of silicon powder is ≥99.8%, and the particle size of silicon powder is 2-10μm.
[0007] A method for manufacturing a lightweight ceramic bearing, used to produce the aforementioned ceramic bearing, includes the following steps: S1. Take hyperbranched polycarbosilane, divinylbenzene, and xylene, and mix them using a combination of wet dispersion and dry mixing to prepare a liquid precursor mixture; S2. Take carbon fiber and use a three-dimensional braiding machine to prepare fiber preforms by using a ring braiding or spiral winding process, in the form of orthogonal braiding or multi-angle lay-up. S3. Take the bearing ring mold and trim the fiber preform according to the mold size; S4. Place the fiber preform into the bearing ring mold, fill the mold with phenolic resin, and then heat the mold to obtain the C / C composite preform. S5. Place the C / C composite preform in a vacuum pressure impregnation furnace, impregnate the liquid precursor mixture into the C / C composite preform, and then place the impregnated C / C composite preform in a vacuum induction ultra-high temperature sintering furnace for silicon infiltration. S6. Repeat S5. Every 3 repetitions of S5, perform a 3-6 hour high-temperature opening and graphitization treatment at 1800℃. Repeat S5 a total of 11-14 times to obtain the bearing ring. S7. The inner ring and outer ring are obtained through S1-S6. After grinding the inner ring and outer ring, the inner ring, outer ring, ceramic ball and cage are assembled.
[0008] Furthermore, in S1, materials are selected according to the mass ratio of hyperbranched polycarbosilane 59-62%, divinylbenzene 20-24%, and xylene 15-18%. First, the hyperbranched polycarbosilane and divinylbenzene are dissolved in xylene as a solvent for wet mixing. Then, the xylene is evaporated and solvent-free dry mixing is carried out to obtain a liquid precursor mixture.
[0009] Furthermore, in S2, the volume of carbon fibers in the fiber preform is 30%-32% of the total volume of the fiber preform.
[0010] Furthermore, in S4, the heating process is as follows: the temperature inside the mold is raised to 80°C at a temperature rise rate of 1.5°C / min, and then held at 80°C for 60 min; then the temperature inside the mold is raised to 120°C at a temperature rise rate of 1°C / min, and held at 2-5 MPa pressure for 30 min; then the temperature inside the mold is raised to 150°C at a temperature rise rate of 1°C / min, and held at 20 MPa pressure for 30 min to obtain the C / C composite preform.
[0011] Furthermore, in S5, the silicon infiltration temperature during the silicon infiltration process is 1700℃, the silicon infiltration holding time is 30min, and the vacuum degree is 50Pa.
[0012] Furthermore, during the silicon infiltration process, silicon powder is melted and infiltrated into the composite preform as a supplementary silicon source for the reaction of hyperbranched polycarbosilane to generate the SiC matrix.
[0013] Furthermore, in S6, the pyrolytic carbon within the material is reconstructed through high-temperature pore-opening treatment, transforming closed pores into open pores.
[0014] Furthermore, in S7, CBN grinding wheels are used to grind the end faces of the bearing rings, and brown corundum grinding wheels are used to grind the inner and outer diameters of the bearing rings; during assembly, the inner ring, outer ring, ceramic balls, and cage are assembled using a cold assembly method.
[0015] The beneficial effects of this invention are as follows: 1. The inner and outer rings are made of C / C-SiC ceramic composite material, the ceramic balls are made of Si3N4 ceramic material, and the cage is made of polytetrafluoroethylene material, forming a bearing structure with complementary performance; C / C-SiC ceramic has a low density, approximately 2T / m³. 3 It weighs only about 25% of traditional metal bearings and about 60% of traditional ceramic bearings, significantly reducing the overall weight of bearings and meeting the lightweight requirements of special environments. C / C-SiC ceramics can maintain stable mechanical properties and friction coefficients above 1000℃, and its wear resistance is better than that of traditional metal bearings, extending the bearing service life. It can work stably in ultra-high temperature and ultra-low temperature environments, making the bearings applicable to special environments such as spacecraft and space stations where ultra-high temperature and ultra-low temperature conditions and extremely high lightweight requirements are required. C / C-SiC ceramic materials have pores, and during the friction process, the gas or trace amount of lubricant in the pores can play a self-lubricating role, reducing friction and wear and reducing dependence on external lubrication. It is suitable for special scenarios such as spacecraft and space stations where lubrication is difficult or high cleanliness requirements are required.
[0016] 2. The fiber preform is made by ring weaving or spiral winding process, which has higher structural strength and is conducive to improving the service performance of ceramic bearings. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of this utility model or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this utility model. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 It is the fiber preform described in this invention; Figure 2 This is the fracture microstructure of the ceramic composite material described in this invention; Figure 3 This is the second fracture microstructure of the ceramic composite material described in this invention; Figure 4 This is the fracture microstructure of the ceramic composite material described in this invention. Detailed Implementation
[0019] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.
[0020] In a first aspect, the present invention provides a lightweight ceramic bearing, comprising an inner ring, an outer ring, a cage, and ceramic balls. The inner and outer rings are both made of C / C-SiC ceramic material, the ceramic balls are made of Si3N4 ceramic material, and the cage is made of polytetrafluoroethylene material. The raw materials of the C / C-SiC ceramic material include hyperbranched polycarbosilane (Tri-ImPCS), divinylbenzene (DVB), xylene, carbon fibers, phenolic resin, and silicon powder. The C / C-SiC ceramic material exhibits a typical three-level structure of "fiber-interface-matrix". In this structure, carbon fibers constitute the skeleton network structure of the ceramic material, and the SiC matrix formed by the reaction of hyperbranched polycarbosilane and silicon powder with carbon infiltrates into the skeleton network structure wraps the fiber bundles. Residual free carbon fills the pores of the SiC matrix. Pores in ceramic materials are mainly classified into three types: macropores (10-50 μm) between fiber bundles, which are determined by the woven structure; micropores (1-5 μm) within the matrix, which are formed by the cracking and shrinkage of the precursor; and interfacial nanopores (<500 nm), which are caused by the mismatch of thermal expansion coefficients.
[0021] Furthermore, in the raw materials for C / C-SiC ceramic materials, the carbon fiber diameter is 7μm; the solid content of the phenolic resin is ≥50%, and the free phenol content of the phenolic resin is ≤15%; the purity of the silicon powder is ≥99.8%, and the particle size of the silicon powder is 2-10μm. In addition, the hyperbranched polycarbosilane needs to be ball-milled into powder and passed through a 100-mesh sieve.
[0022] Secondly, the present invention provides the following three embodiments of the manufacturing method of the above-mentioned lightweight ceramic bearing.
[0023] Example 1: A method for manufacturing a lightweight ceramic bearing, comprising the following steps: S1. The hyperbranched polycarbosilane, divinylbenzene, and xylene are mixed using a combination of wet dispersion and dry mixing at a mass ratio of 62% and 23% respectively, to form a homogeneous liquid precursor mixture. The resulting mixed solution has a viscosity of 600-800 MPa·s at a temperature of 40-60℃. Xylene is used as a solvent to dissolve the hyperbranched polycarbosilane and divinylbenzene, adjusting the viscosity of the hyperbranched polycarbosilane / divinylbenzene system to ensure uniform dispersion during mixing and guarantee the homogeneity of the reaction.
[0024] Specifically, in the wet dispersion and dry mixing operations, wet dispersion is performed first, in which hyperbranched polycarbosilane and divinylbenzene are dissolved in xylene solvent and fully dispersed by stirring, sonication, etc., to form a uniform solution, ensuring that each component is evenly distributed at the microscopic level; then dry mixing is performed, in which the xylene solvent is evaporated at a certain temperature, allowing the remaining hyperbranched polycarbosilane and divinylbenzene to be further mixed evenly, to obtain a uniform liquid precursor mixture.
[0025] S2. High-strength carbon fibers are taken and prepared using a three-dimensional braiding machine with ring braiding or spiral winding process and multi-angle (±45°) layering. The volume of carbon fibers in the fiber preform is 30% of the total volume of the fiber preform. The fiber preform is then sprayed with low-viscosity epoxy resin to prevent it from loosening and deforming.
[0026] S3. Take the bearing ring mold, trim the fiber preform according to the mold size. If splicing is required, use overlapping and ensure that the fibers at the joint are continuous.
[0027] S4. Apply the release agent to the inner surface of the mold, place the fiber preform into the bearing ring mold, spray low-viscosity epoxy resin, then fill the mold with phenolic resin and heat the mold to obtain the C / C composite preform. Specifically, the heating process is as follows: raise the temperature inside the mold to 80℃ at a temperature rise rate of 1.5℃ / min, and then hold at 80℃ for 60min; then raise the temperature inside the mold to 120℃ at a temperature rise rate of 1℃ / min, and hold at 2-5MPa pressure for 30min; then raise the temperature inside the mold to 150℃ at a temperature rise rate of 1℃ / min, and hold at 20MPa pressure for 30min to obtain the C / C composite preform.
[0028] S5. Place the C / C composite preform in a vacuum pressure impregnation furnace and impregnate the C / C composite preform with a liquid precursor mixture under a certain pressure. Then, place the impregnated C / C composite preform in a vacuum induction ultra-high temperature sintering furnace for silicon infiltration. The C / C composite preform crosslinks, solidifies, and decomposes at high temperature. The hyperbranched polycarbosilane in the liquid precursor reacts with carbon to generate a SiC matrix, thus obtaining C / C-SiC ceramics. The parameters selected during the silicon infiltration process are as follows: silicon infiltration temperature 1700℃, silicon infiltration holding time 30min, and vacuum degree 50Pa.
[0029] Among them, hyperbranched polycarbosilane, as a SiC precursor, can improve crosslinking density through its branched structure, resulting in higher ceramic yield after pyrolysis. During high-temperature silicon infiltration, it reacts with carbon to generate a SiC matrix, providing ceramics with properties such as hardness and wear resistance. Its good fluidity and high ceramic yield are beneficial to the preparation process. Divinylbenzene, as a crosslinking agent, undergoes a hydrosilylation reaction with the Si-H bonds in hyperbranched polycarbosilane to form a three-dimensional network structure, inhibiting the release of volatile components from pyrolysis. During the mixing process, it promotes the crosslinking reaction between hyperbranched polycarbosilane and other components, which helps to form a stable network structure and enhance the overall performance of ceramic materials.
[0030] During the silicon infiltration stage, silicon powder can replenish the silicon source and fill the silicon vacancies generated by the cracking of hyperbranched polycarbosilane, ensuring a complete carbonization reaction (3C + Si → SiC + 2C). This results in a denser and more uniform SiC matrix, improving the density and performance of the ceramic. Furthermore, silicon powder with a purity ≥99.8% and a particle size of 2-10 μm allows molten silicon to penetrate into the micropores. Appropriate purity and particle size facilitate uniform diffusion and reaction during silicon infiltration, reducing residual porosity and further ensuring the quality of the ceramic.
[0031] S6. Each completion of S5 constitutes one "impregnation-curing-pyrolysis" cycle. Every three "impregnation-curing-pyrolysis" cycles, a 6-hour high-temperature pore-opening and graphitization treatment at 1800℃ is performed. If less than three "impregnation-curing-pyrolysis" cycles are completed, the high-temperature pore-opening and graphitization treatment is not performed. A total of 14 "impregnation-curing-pyrolysis" cycles and 4 high-temperature pore-opening and graphitization treatments are performed to obtain the bearing ring based on C / C-SiC ceramic. During the preparation process, some closed pores or incompletely interconnected structures exist inside the ceramic material. High-temperature treatment can reconstruct the pyrolytic carbon, turning some closed pores into open pores (pore size increased by 15-20%), making these pores interconnected or connected to the outside world. This facilitates the entry of liquid precursor mixture into the pores during impregnation and the formation of a structure filled with free carbon within the pores, which helps improve self-lubricating properties. High-temperature graphitization of the carbon matrix can transform the disordered carbon structure into ordered graphite crystals, which can improve thermal conductivity (40%) and oxidation resistance.
[0032] S7. The inner and outer rings are made through S1-S6. The inner and outer rings are ground. The end face of the bearing ring is ground with a CBN grinding wheel, and the inner and outer diameters of the bearing ring are ground with a brown corundum grinding wheel. The inner ring, outer ring, ceramic ball and cage are assembled using the cold assembly method to ensure that the clearance of the ceramic bearing meets the design requirements.
[0033] Example 2: A method for manufacturing a lightweight ceramic bearing, comprising the following steps: S1. The mixture is prepared by a combination of wet dispersion and dry mixing according to the mass ratio of hyperbranched polycarbosilane 61%, divinylbenzene 23%, and xylene 16% to form a uniform liquid precursor mixture; the viscosity of the resulting mixed solution is 600-800 MPa·s at a temperature of 40-60℃.
[0034] S2. Take high-strength carbon fiber and use a three-dimensional braiding machine to adopt a ring braiding or spiral winding process, and use orthogonal braiding (0° / 90°) layup to prepare a fiber preform. The volume of carbon fiber in the fiber preform is 31% of the total volume of the fiber preform. Spray the fiber preform with low viscosity epoxy resin to prevent it from loosening and deforming.
[0035] S3. Take the bearing ring mold, trim the fiber preform according to the mold size. If splicing is required, use overlapping and ensure that the fibers at the joint are continuous.
[0036] S4. Apply the release agent to the inner surface of the mold, place the fiber preform into the bearing ring mold, spray low-viscosity epoxy resin, then fill the mold with phenolic resin and heat the mold to obtain the C / C composite preform. Specifically, the heating process is as follows: raise the temperature inside the mold to 80℃ at a temperature rise rate of 1.5℃ / min, and then hold at 80℃ for 60min; then raise the temperature inside the mold to 120℃ at a temperature rise rate of 1℃ / min, and hold at 2-5MPa pressure for 30min; then raise the temperature inside the mold to 150℃ at a temperature rise rate of 1℃ / min, and hold at 20MPa pressure for 30min to obtain the C / C composite preform.
[0037] S5. Place the C / C composite preform in a vacuum pressure impregnation furnace and impregnate the liquid precursor mixture into the C / C composite preform. Then, place the impregnated C / C composite preform in a vacuum induction ultra-high temperature sintering furnace for silicon infiltration. The C / C composite preform crosslinks, solidifies, and pyrolyzes at high temperature. The hyperbranched polycarbosilane in the liquid precursor reacts with carbon to generate a SiC matrix, thus obtaining C / C-SiC ceramics. The parameters selected during the silicon infiltration process are as follows: silicon infiltration temperature 1700℃, silicon infiltration holding time 30min, and vacuum degree 50Pa.
[0038] S6. Each completion of S5 constitutes one "impregnation-curing-pyrolysis" cycle; every three "impregnation-curing-pyrolysis" cycles, a 6-hour high-temperature pore-opening and graphitization treatment is performed; a total of 12 "impregnation-curing-pyrolysis" cycles and 4 high-temperature pore-opening and graphitization treatments are performed to obtain bearing rings based on C / C-SiC ceramics.
[0039] S7. The inner and outer rings are made through S1-S6. The inner and outer rings are ground. The end face of the bearing ring is ground with a CBN grinding wheel, and the inner and outer diameters of the bearing ring are ground with a brown corundum grinding wheel. The inner ring, outer ring, ceramic ball and cage are assembled using the cold assembly method to ensure that the clearance of the ceramic bearing meets the design requirements.
[0040] Example 3: A method for manufacturing a lightweight ceramic bearing, comprising the following steps: S1. The mixture is prepared by a combination of wet dispersion and dry mixing according to the mass ratio of hyperbranched polycarbosilane 59%, divinylbenzene 23%, and xylene 18% to form a uniform liquid precursor mixture; the viscosity of the resulting mixed solution is 600-800 MPa·s at a temperature of 40-60℃.
[0041] S2. High-strength carbon fibers are taken and prepared into fiber preforms using a three-dimensional braiding machine with ring braiding or spiral winding process and multi-angle (±45°) layering. The volume of carbon fibers in the fiber preform is 32% of the total volume of the fiber preform. The fiber preform is then sprayed with low-viscosity epoxy resin to prevent it from loosening and deforming.
[0042] S3. Take the bearing ring mold, trim the fiber preform according to the mold size. If splicing is required, use overlapping and ensure that the fibers at the joint are continuous.
[0043] S4. Apply the release agent to the inner surface of the mold, place the fiber preform into the bearing ring mold, spray low-viscosity epoxy resin, then fill the mold with phenolic resin and heat the mold to obtain the C / C composite preform. Specifically, the heating process is as follows: raise the temperature inside the mold to 80℃ at a temperature rise rate of 1.5℃ / min, and then hold at 80℃ for 60min; then raise the temperature inside the mold to 120℃ at a temperature rise rate of 1℃ / min, and hold at 2-5MPa pressure for 30min; then raise the temperature inside the mold to 150℃ at a temperature rise rate of 1℃ / min, and hold at 20MPa pressure for 30min to obtain the C / C composite preform.
[0044] S5. Place the C / C composite preform in a vacuum pressure impregnation furnace and impregnate the liquid precursor mixture into the C / C composite preform. Then, place the impregnated C / C composite preform in a vacuum induction ultra-high temperature sintering furnace for silicon infiltration. The C / C composite preform crosslinks, solidifies, and pyrolyzes at high temperature. The hyperbranched polycarbosilane in the liquid precursor reacts with carbon to generate a SiC matrix, thus obtaining C / C-SiC ceramics. The parameters selected during the silicon infiltration process are as follows: silicon infiltration temperature 1700℃, silicon infiltration holding time 30min, and vacuum degree 50Pa.
[0045] S6. Each completion of S5 constitutes one "impregnation-curing-pyrolysis" cycle; every three "impregnation-curing-pyrolysis" cycles, a 6-hour high-temperature pore-opening and graphitization treatment is performed; a total of 11 "impregnation-curing-pyrolysis" cycles and 3 high-temperature pore-opening and graphitization treatments are performed to obtain bearing rings based on C / C-SiC ceramics.
[0046] S7. The inner and outer rings are made through S1-S6. The inner and outer rings are ground. The end face of the bearing ring is ground with a CBN grinding wheel, and the inner and outer diameters of the bearing ring are ground with a brown corundum grinding wheel. The inner ring, outer ring, ceramic ball and cage are assembled using the cold assembly method to ensure that the clearance of the ceramic bearing meets the design requirements.
[0047] The ceramic bearings prepared in Examples 1-3 were subjected to performance tests using conventional methods, and were compared with traditional all-ceramic (Si3N4) bearings and metal (steel) bearings of the same specifications and dimensions in the prior art under the same conditions. The test results are shown in Table 1.
[0048] Table 1 Performance indicators of lightweight all-ceramic bearings in Examples 1-3 As can be seen from Table 1, the lightweight all-ceramic bearing of the present invention has a significantly lower density and a significantly higher hardness compared to the metal bearing; compared to the traditional all-ceramic (Si3N4), the lightweight all-ceramic bearing has a significantly lower density and a significantly higher fracture toughness.
[0049] Table 2 shows the performance parameters of C / C-SiC ceramics under ultra-high temperature and ultra-low temperature environments. As can be seen from Table 2, the lightweight all-ceramic bearing of this invention maintains stable mechanical properties and friction coefficients under both high and low temperature environments, extending the bearing's service life. It can operate stably under ultra-high temperature and ultra-low temperature environments; and its wear resistance is superior to that of metal bearings. The ceramic test results presented in this paper are based on the ceramic bearing test results obtained according to (“Influence Factors on the Density of C / C-SiC Composite Materials”, Journal of Aeronautical Materials, Chen Zhiyong et al., Vol. 41, No. 1, pp. 67-73, 2021).
[0050] Table 2 Comparison of performance indicators of lightweight all-ceramic bearings under different environments in Example 1 Figure 1 The image shows a fiber preform in which carbon fibers are uniformly distributed, serving as a skeletal network for the ceramic composite material. Figure 2-4 The image shows the fracture microstructure of the ceramic composite material as observed by an electron microscope. Figure 2 , Figure 3 , Figure 4 The carbon fibers underwent 9, 10, and 11 cycles of the "impregnation-crosslinking-pyrolysis" process, respectively. The carbon fibers were long columnar, the SiC phase was a dark gray area, the free Si phase was a bright white area, and the pores were black areas. As shown in the attached figures, the pores (black areas) gradually decreased with increasing cycle length; the fiber pull-out phenomenon decreased with increasing cycle length, indicating that the bonding force between the SiC matrix and the carbon fibers improved, and the reinforcing and toughening effect of the carbon fibers was significant. Figures 3 and 4 show the results. Figure 4 The fact that the dark gray SiC phase did not change much indicates that the pores of the preform were filled and carbonized to the maximum extent after 11 cycles, and at least 11 cycles are required.
[0051] During the preparation process, some closed pores or incompletely interconnected structures exist inside the ceramic material. High-temperature treatment can reconstruct the pyrolytic carbon, turning some closed pores into open pores (pore diameter increases by 15-20%), making these pores interconnected or connected to the outside world. This facilitates the entry of the liquid precursor mixture into the pores during impregnation and the formation of a structure filled with free carbon within the pores, which helps improve the self-lubricating performance.
[0052] Hyperbranched polycarbosilanes, as SiC precursors, exhibit improved crosslinking density due to their branched structure, resulting in higher ceramic yields after pyrolysis. During high-temperature silicon infiltration, they react with carbon to form a SiC matrix, providing the ceramics with properties such as hardness and wear resistance. Their good flowability and high ceramic yield facilitate the preparation process. Divinylbenzene, acting as a crosslinking agent, undergoes hydrosilylation with the Si-H bonds in hyperbranched polycarbosilanes, forming a three-dimensional network structure. This inhibits the escape of volatile components during pyrolysis and promotes crosslinking reactions between hyperbranched polycarbosilanes and other components during mixing, contributing to the formation of a stable network structure and enhancing the overall performance of the ceramic material. The high crosslinking properties of hyperbranched polycarbosilanes allow for more thorough ceramic phase transformation during pyrolysis, reducing volatilization losses by 5%-8% compared to ordinary polycarbosilanes. Combined with the 7%-10% yield increase from thorough crosslinking, this results in a total improvement of 12%-18%.
[0053] The inner and outer rings of this invention are made of C / C-SiC ceramic composite material, the ceramic balls are made of Si3N4 ceramic material, and the cage is made of polytetrafluoroethylene material, forming a bearing structure with complementary properties; C / C-SiC ceramic has a low density, approximately 2 T / m³. 3 It weighs only about 25% of traditional metal bearings and about 60% of traditional ceramic bearings, significantly reducing the overall weight of the bearing and meeting the lightweight requirements of special environments. C / C-SiC ceramics maintain stable mechanical properties and friction coefficients above 1000℃, and its wear resistance is superior to traditional metal bearings, extending bearing life. It can operate stably in ultra-high temperature and ultra-low temperature environments, enabling the bearings to be used in special environments such as spacecraft and space stations where ultra-high temperature and ultra-low temperature conditions and extremely high lightweight requirements exist. The fiber preform is made using ring weaving or spiral winding processes, resulting in higher structural strength, which is beneficial to improving the service performance of ceramic bearings.
[0054] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A lightweight ceramic bearing, comprising an inner ring, an outer ring, a cage, and ceramic balls, characterized in that: Both the inner and outer rings are made of C / C-SiC ceramic material, the ceramic balls are made of Si3N4 ceramic material, and the cage is made of polytetrafluoroethylene material. The raw materials of C / C-SiC ceramic material include hyperbranched polycarbosilane, divinylbenzene, xylene, carbon fiber, phenolic resin, and silicon powder. C / C-SiC ceramic material has a skeleton network structure composed of carbon fiber and a SiC matrix that wraps the fiber bundles of the skeleton network structure. The SiC matrix is obtained by reacting hyperbranched polycarbosilane and silicon powder that have penetrated into the skeleton network structure with carbon. Free carbon is filled in the pores of the SiC matrix.
2. The lightweight ceramic bearing according to claim 1, characterized in that: In the raw materials of C / C-SiC ceramic materials, the diameter of carbon fiber is 7μm; the solid content of phenolic resin is ≥50%, and the free phenol content of phenolic resin is ≤15%; the purity of silicon powder is ≥99.8%, and the particle size of silicon powder is 2-10μm.
3. A method for manufacturing a lightweight ceramic bearing, used to produce the ceramic bearing according to any one of claims 1-2, characterized in that, Includes the following steps: S1. Take hyperbranched polycarbosilane, divinylbenzene, and xylene, and mix them using a combination of wet dispersion and dry mixing to prepare a liquid precursor mixture; S2. Take carbon fiber and use a three-dimensional braiding machine to prepare fiber preforms by using a ring braiding or spiral winding process, in the form of orthogonal braiding or multi-angle lay-up. S3. Take the bearing ring mold and trim the fiber preform according to the mold size; S4. Place the fiber preform into the bearing ring mold, fill the mold with phenolic resin, and then heat the mold to obtain the C / C composite preform. S5. Place the C / C composite preform in a vacuum pressure impregnation furnace, impregnate the liquid precursor mixture into the C / C composite preform, and then place the impregnated C / C composite preform in a vacuum induction ultra-high temperature sintering furnace for silicon infiltration. S6. Repeat S5. Every 3 repetitions of S5, perform a 3-6 hour high-temperature opening and graphitization treatment at 1800℃. Repeat S5 a total of 11-14 times to obtain the bearing ring. S7. The inner ring and outer ring are obtained through S1-S6. After grinding the inner ring and outer ring, the inner ring, outer ring, ceramic ball and cage are assembled.
4. The method for manufacturing a lightweight ceramic bearing according to claim 3, characterized in that: In S1, materials are prepared according to the mass ratio of hyperbranched polycarbosilane 59-62%, divinylbenzene 20-24%, and xylene 15-18%. First, the hyperbranched polycarbosilane and divinylbenzene are dissolved in xylene as a solvent for wet mixing. Then, the xylene is evaporated and solvent-free dry mixing is carried out to obtain a liquid precursor mixture.
5. The method for manufacturing a lightweight ceramic bearing according to claim 3, characterized in that: In S2, the volume of carbon fibers in the fiber preform is 30%-32% of the total volume of the fiber preform.
6. The method for manufacturing a lightweight ceramic bearing according to claim 3, characterized in that: In S4, the heating process is as follows: the temperature inside the mold is raised to 80°C at a temperature rise rate of 1.5°C / min, and then held at 80°C for 60 min; then the temperature inside the mold is raised to 120°C at a temperature rise rate of 1°C / min, and held at 2-5 MPa pressure for 30 min; then the temperature inside the mold is raised to 150°C at a temperature rise rate of 1°C / min, and held at 20 MPa pressure for 30 min to obtain the C / C composite preform.
7. The method for manufacturing a lightweight ceramic bearing according to claim 3, characterized in that: In S5, the silicon infiltration temperature during the silicon infiltration process is 1700℃, the silicon infiltration holding time is 30min, and the vacuum degree is 50Pa.
8. The method for manufacturing a lightweight ceramic bearing according to claim 7, characterized in that: During the silicon infiltration process, silicon powder is melted and infiltrated into the composite preform as a supplementary silicon source for the reaction of hyperbranched polycarbosilane to generate the SiC matrix.
9. The method for manufacturing a lightweight ceramic bearing according to claim 1, characterized in that: In S6, the pyrolytic carbon within the material is reconstructed through high-temperature opening treatment, transforming closed pores into open pores.
10. The method for manufacturing a lightweight ceramic bearing according to claim 3, characterized in that: In S7, CBN grinding wheels are used to grind the end faces of the bearing rings, and brown corundum grinding wheels are used to grind the inner and outer diameters of the bearing rings. During assembly, the inner ring, outer ring, ceramic balls, and cage are assembled using a cold assembly method.